2014
DOI: 10.1186/1471-2458-14-815
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and multimorbidity in a representative sample of the Spanish population

Abstract: BackgroundIn the context of population aging, visual impairment has emerged as a growing concern in public health. However, there is a need for further research into the relationship between visual impairment and chronic medical conditions in the elderly. The aim of our study was to examine the relationship between visual impairment and three main types of co-morbidity: chronic physical conditions (both at an independent and additive level), mental health and cognitive functioning.MethodsData were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 77 publications
4
50
1
Order By: Relevance
“…Most of the previous research in this area has focused on cognition rather than dementia [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Within cross-sectional studies, the results show either a significant association between VI and cognition [2][3][4][5][6][7][8] or no association [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous research in this area has focused on cognition rather than dementia [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Within cross-sectional studies, the results show either a significant association between VI and cognition [2][3][4][5][6][7][8] or no association [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The leading cause of VL is uncorrected refractive error [1], easily avoidable with corrective eyeglasses, lenses or refractive surgery. VL has been associated with cognitive impairment, but mainly in cross-sectional studies [2][3][4][5][6][7][8][9][10], whereas longitudinal studies have shown conflicting results [11][12][13][14][15][16]. Furthermore, little is known about the longitudinal association between VL and dementia, with only one previous study among participants aged 71 and older, showing that those who perceived that their vision was good or excellent had a lower risk of developing dementia [17].…”
Section: Introductionmentioning
confidence: 99%
“…This study adopted a novel dimensional approach to extend past research which has previously established cross-sectional (Court et al, 2014;Garin et al, 2014;Hayman et al, 2007) and…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of sensory loss and mental health literature has focused on VL and depression. Prior research consistently demonstrates that older adults with VL have an increased risk of depression . Possible mechanisms include a reduction in social activities and subsequent social isolation .…”
Section: Introductionmentioning
confidence: 99%
“…Prior research consistently demonstrates that older adults with VL have an increased risk of depression. [9][10][11][12][13] Possible mechanisms include a reduction in social activities and subsequent social isolation. 14,15 It has also previously been demonstrated that depression and worse mental health outcomes are observed in those with poorer mobility and physical health, [16][17][18] as well as being more common amongst women 17 and those who are less educated and unmarried or live alone.…”
Section: Introductionmentioning
confidence: 99%